Development and formative evaluation of computer-assisted instruction on selected topics in general biology - Hojilla, Ma. Elena Bernadette Pardo (Animo Repository, 1999)
This study aims to design, develop and conduct a formative evaluation of CAI software serving as a supplementary material in teaching selected topics in general biology.This study involves two phases, namely: (1) the design and development stage and (2) the evaluation stage of the CAI software. Phase I resulted in the production of the four (4) CAI modules on cell reproduction, cell cycle, mitosis and meiosis. To achieve the content validation of the CAI modules, these were examined, evaluated, and edited by a panel of experts on instructional materials preparation, development and production as well as professors specializing the field of biology. Comments and suggestions of these validators and/or evaluators were collated and considered for the revision of the CAI modules. Using Fry's Readability Graph, the readability of the CAI modules was evaluated and was found to have reading levels appropriate for the intended users. In the evaluation stage of Phase II, three evaluation instruments were developed and validated. These are: (1) Evaluation Guide for Students, (2) Evaluation Guide for Teachers, and (3) Evaluation Guide for Computer Experts. Three groups of evaluators took part in the formative evaluation of the CAI software, namely: (1) college freshmen students of Systems Plus Computer College in Caloocan City, (2) biology teachers/professors, and (3) computer experts.The formative evaluation made by the student evaluators revealed a highly favorable rating of the CAI learning package in the areas of: (a) objectives, (b) clarity of explanation, (c) test items. Furthermore, the same group of student-evaluators gave a favorable rating of the instructional material in terms of (a) subject matter, and (b) design characteristics. The formative evaluation conducted by biology teacher-evaluators showed that five (5) areas of the CAI learning package were rated highly favorable. These are (a) objectives, (b) subject matter, (c) clarity of explanation, (d) test items, and (e) adaptability. On the other hand, one area, design characteristics, was rated favorable. The formative evaluation made by computer experts revealed a favorable rating for all three (3) areas of the design characteristics of the CAI learning package. These are (a) usability, (b) functionality, and (c) interface design/development.